The Effect of Using Plastic Strips and Sheets on the Properties of Slurry Infiltrated Fiber Concrete - Najeeb, A. M.; Fawzi, N. M. (Engineering, Technology & Applied Science Research, 2021)
Slurry Infiltrated Fiber Concrete (SIFCON) is a high-strong material that is regarded as a unique type of high fiber content concrete. This paper aims to study the influence of the use of plastic strips and plastic sheets in the SIFCON slurry. Three sets (normal SIFCON as control, SIFCON with plastic strips, and SIFCON with plastic sheet), in a 1:1.08 cement-sand ratio by weight has been used with water to cement ratio (w/c) by weight equal to 0.3, and superplasticizer equal to 1% by weight. In addition, 6% by volume crimped steel fibers with an aspect ratio of 60 were applied and 1.34% by volume plastic was used, in strips of 5×1cm for both prism and cube samples and in sheets of 25×5cm and 7×7cm for prism and cube samples respectively. The compressive and flexural strength tests studies were conducted on typical cubes of 10×10×10cm and prisms of 40×7×7cm respectively to find out the way the plastic affects the SIFCON properties. The results indicate that the models with plastic sheets placed in SIFCON slurry give the highest compressive and flexural strength whereas the models with plastic strips gave the lowest. The difference percentages in compressive and flexural strength were -27.3, 8, -3.8 and 66.6% for all sets respectively when compared to the control set (using no plastic).